(untitled) - Food and Agriculture Organization of the United nations (Rome, 2007)
This document has been prepared to enhance the transparency of the practices and procedures applied by FAO and WHO to deliver scientific advice. It illustrates that the same basic principles and rules apply to the different expert groups such as the Joint FAO/WHO Expert Committee on Food Additives (JECFA), the Joint FAO/WHO Expert meetings on Pesticide Residues (JMPR), the Joint FAO/WHO Expert meetings on Microbiological Risk Assessment (JEMRA) and consultations and meeting organized in response to specific ad hoc requests or emergency situations. (Also published in Arabic, Chinese, French and Spanish)
Keywords: Food,Nutrition,Thực phẩm,Dinh dưỡng; Safety measures,Biện pháp an toàn